Mapping the Spatial Footprint of Sea Breeze Winds in the Southeastern United States. Issue 7 (5th April 2023) - Bao, Shaowu; Pietrafesa, Leonard; Gayes, Paul; Noble, Stephen; Viner, Brian; Qian, Jian‐Hua; Werth, David; Mitchell, Grant; Burdette, Savannah
Abstract: Sea breeze winds are observed at various locations worldwide, but the spatially continuous mapping of sea breeze winds is rare. We have developed a scheme to map the areas of the southeastern United States (SEUS) coast influenced by sea breeze winds using a range of surface re‐analysis data to identify their occurrence. Changes in wind direction and dew point temperature are both used to detect a potential sea breeze signature, which is then confirmed by cumuliform clouds seen in satellite images or coastal fronts shown as cohesive lines in radar reflectivity images. Filters are employed to remove onshore winds not induced by the temperature difference between land and sea. From March to September 2019, this scheme identified 134 days with sea breeze occurrence somewhere in the SEUS, a frequency of 63 percent. The number of sea breezes increased from March to July and then decreased to September. Deep inland propagation of sea breezes during this period left footprints in a band parallel to the coastline up to about 220 km inland, after which the sea breeze winds quickly diminished. Comparisons show that the findings using the scheme are consistent with site observations, theoretical estimates, and idealized and semi‐idealized numerical model simulations. Plain Language Summary: A sea breeze wind starts to blow from the ocean toward land during late afternoons and can last into late evenings, nights, and into early morning. It is caused by land‐sea temperature differences. Sea breeze is important along the coast that moves cold, moisture laden sea air masses and particles inland, causing rainstorms. Data sets from coastal locations around the world show sea breeze winds move inland, but it is rare to map their spatial distribution due to a lack of continuous in‐situ weather data. We use a high‐resolution near‐surface wind and moisture model product along with satellite and radar images to find the locations that sea breeze winds reach onshore. This method was tested from March to September 2019 in the southeastern US (SEUS). Sea breezes occurred 63% of the days in the SEUS during this period. Sea breezes increased from March to July, and then decreased thereafter. When sea breezes moved inland during this period, they form a band parallel to the coast for up to around 220 km inland. After that, the sea breeze winds disappear. When compared, the scheme's results are in line with in‐situ observations, theoretical estimates, and idealized and semi‐idealized model simulations. Key Points: The combination of surface reanalysis and remote sensing data can be used to map the spatial distribution of sea breeze winds Sixty‐three percent of the days had sea breezes in the southeastern US (SEUS) from March–September 2019, increasing from March to July and then decreasing The SEUS sea breeze winds leave footprints in a band parallel to the coastline up to about 220 km inland, then quickly diminish